The Oslo Sports Trauma Research Center questionnaire on health problems: a new approach to prospective monitoring of illness and injury in elite athletes - Clarsen, B.; Rønsen, O.; Myklebust, G.; Flørenes, T. W.; Bahr, R. (British Journal of Sports Medicine, 2014)
Background: Little information exists on the illness and injury patterns of athletes preparing for the Olympic and Paralympic Games. Among the possible explanations for the current lack of knowledge are the methodological challenges faced in conducting prospective studies of large, heterogeneous groups of athletes, particularly when overuse injuries and illnesses are of concern. Objective: To describe a new surveillance method that is capable of recording all types of health problems and to use it to study the illness and injury patterns of Norwegian athletes preparing for the 2012 Olympic and Paralympic Games. Methods: A total of 142 athletes were monitored over a 40-week period using a weekly online questionnaire on health problems. Team medical personnel were used to classify and diagnose all reported complaints. Results: A total of 617 health problems were registered during the project, including 329 illnesses and 288 injuries. At any given time, 36% of athletes had health problems (95% CI 34% to 38%) and 15% of athletes (95% CI 14% to 16%) had substantial problems, defined as those leading to moderate or severe reductions in sports performance or participation, or time loss. Overuse injuries represented 49% of the total burden of health problems, measured as the cumulative severity score, compared to illness (36%) and acute injuries (13%). Conclusions: The new method was sensitive and valid in documenting the pattern of acute injuries, overuse injuries and illnesses in a large, heterogeneous group of athletes preparing for the Olympic and Paralympic Games.